DIGITAL MUSIC USE AS ECOLOGICAL THINKING: METADATA AND HISTORICISED LISTENING - Pedersen, Andreas Helles (The Nordic Journal of Aesthetics, 2020)
In claiming that metadata possess the power to put historical awareness into the act of listening, this article examines digital music use as an aesthetic situation driven by potentialities of becoming. Working from a theoretical foundation amalgamating digital music archives and metadata as environments the article discusses Georgina Born’s notion of musical assemblages alongside the concept of virtuality, and by letting these meet the article argues for a musical assemblage built from sensibilities of becoming rather than layers of mediation. The inner workings of digital music use constitute an ecology in which recorded music history moves and reconnects, and this makes the historicity of recorded music be fluid, thus turning listening into a historicised action. In exemplifying this, the article discusses some of the strategic programming of metadata on the digital music platform Diskoteket, and through an analysis of sampled music, the prospects of recorded music’s historicity are shown as affective capacities.